The Role of Visual Aids in Teaching English - Hermansyah, Hermansyah (Jurnal Dosen Universitas PGRI Palembang)
This paper focused on the role of visual aids in teaching English. A visual aid is an object or representation that may be used to clarify or enhance understanding of a concept or process.The role of visual aids are : (1) Visual aids are learning tools that educators and presenters use to convey an idea more effectively, (2) visual aids is that they help an audience use their visual capacity, (3) Visual aids are key tools in learning and development since they help increase a students interest in a subject, (4) that they enhance learning because interactive effects can be used to reinforce the material learned, and (5) Visual aids help emphasize a point, which is another benefit to using them. The use visual aids can be benefical if the role of teacher used it actively.